Rancang Bangun Aplikasi “Unifiction” dengan Pendekatan Design Thinking untuk Memudahkan Akses Membaca dan Mengunggah Karya Novel Digital - Putra, Anak Agung Adi Wiryya; Frakasa, Meizaluna Aurelia; Darmawan, Pramudya Figo (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The development of the digital novel application "UniFiction" aims to enhance reading interest among Indonesian citizens, which remains relatively low. Statistical data reveals that only 10% of the population regularly engages in book reading. Factors contributing to low reading interest include difficulties locating books in libraries, inadequate infrastructure, and high costs associated with physical books. The application features a minimalist interface that facilitates access to diverse reading sources while serving as a platform for users to express their creativity through writing. The design approach employed Design Thinking methodology involving ten respondents in the usability testing process. The application design achieved a SUS score of 85.5. The expected outcome of the UniFiction application is to enhance reading and writing interest within the community while supporting literacy improvement efforts and reading culture development in Indonesia.